A League Table of Teenage Births in Rich Nations - UNICEF Innocenti Research Centre (United Nations, 2001)
This publication presents the most up-to-date and comprehensive survey on teenage birth rates in the industrialized world. It attempts to analyze why some countries have teenage birth rates that are as much as ten or even fifteen times higher than others.